2022
DOI: 10.1021/acs.nanolett.2c01538
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Behaviors of Supported Nanoparticles Related to Spatial Location by a Quasi-Four-Dimensional TEM

Abstract: The performance degradation via sintering phenomenon is a critical issue for the application of supported nanoparticles in industrial catalysis. However, the challenges to combine in situ stimulation and three-dimensional (3D) characterization hinder a profound understanding of sintering behaviors, thus the effect of spatial location on nanoparticles sintering has long been neglected. Herein, based on a homemade holder integrated with in situ Joule heating and electron tomography, a quasi-four-dimensional (4D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In situ TEM has also been used to study the annealing of single atom catalysts (SACs). Poerwoprajitno et al 105 monitored the dispersion of Pt nano-islands into single atoms on the surface of Ru NPs by in situ TEM in the atmosphere of H 2 up to a temperature of 700 1C. The in situ TEM revealed that Pt islands were ''dissolved'' to form Pt SACs, where the reduction of high surface energy and the formation of strong Pt-Ru bonds result in high MOR activity.…”
Section: In Situ Annealing For Post-synthesismentioning
confidence: 99%
“…In situ TEM has also been used to study the annealing of single atom catalysts (SACs). Poerwoprajitno et al 105 monitored the dispersion of Pt nano-islands into single atoms on the surface of Ru NPs by in situ TEM in the atmosphere of H 2 up to a temperature of 700 1C. The in situ TEM revealed that Pt islands were ''dissolved'' to form Pt SACs, where the reduction of high surface energy and the formation of strong Pt-Ru bonds result in high MOR activity.…”
Section: In Situ Annealing For Post-synthesismentioning
confidence: 99%